Formation of traffic curve of lifting mechanisms taking into account elastic properties of transmissions - Бойко, Андрей Александрович; Шабовта, Михаил Юрьевич; Бойко, Надежда Анатольевна (Technology audit and production reserves, 2015)
Elastic mechanical vibrations adversely affect the control quality, increase the dynamic loads on the lifting mechanisms, contribute to the accumulation of fatigue stresses in the kinematic chains that cause need for their detailed consideration. In the article it is done the synthesis of mathematical relationships that are at any given parameters of lifting mechanisms allows taking into account the elastic properties of the cable transmission, calculate the actual diagram of the lift car, determine the maximum values of velocity, acceleration and jerk that allows to estimate the parameters of passenger elevators, as in the famous classical optimal control law, and in a completely arbitrary control laws. The difference between the maximum accelerations and jerky of passenger lift cabin and their calculated values is determined. The actual maximum acceleration of the passenger lift cabin on 20,0-40,0 % higher than the values determined without taking into account the elastic ties. The increase of the jerk is even more significant and can reach 60,0-140,0 %. The synthesized mathematical relations can be used in case of diagram forming of the lift car moving based on external constraints, such as heat, or if necessary, implementing the "degenerate" triangular diagrams. Based on the analytical expressions can be developed: nonlinear mathematical and physical models, which make it possible, in real time, in a wide range of source data, perform analysis of modes of lift drivers of various types; technical advice on damping lifting mechanisms of arbitrary passenger lifts.